2015
DOI: 10.1097/hcr.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-Induced Ischemic Preconditioning and the Potential Application to Cardiac Rehabilitation

Abstract: Exercise-induced ischemic preconditioning (IPC) can be assessed by the results of the second of sequential exercise tests. Exercise-induced IPC is quantified by using the time to 1-mm ST-segment depression, the rate-pressure product at 1-mm ST-segment depression, the maximal ST-segment depression, and the rate-pressure product at the peak of exercise. Few studies reported whether exercise-induced IPC could be used in cardiovascular rehabilitation. A systematic review of the literature limited to human studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…In relation to Mo, data obtained in the present research could indicate a higher production of free radicals by exercise-induced ischemia-reperfusion in the muscles. This physiological phenomenon can be induced by high intensity muscle contractions [ 24 ], a typical situation among anaerobic physical efforts and, with minor magnitude, by long-duration aerobic exercise, this hypothesis is reinforced by the obtained data, being higher the Mo values among all sportsmen (of all modalities) than among CG.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In relation to Mo, data obtained in the present research could indicate a higher production of free radicals by exercise-induced ischemia-reperfusion in the muscles. This physiological phenomenon can be induced by high intensity muscle contractions [ 24 ], a typical situation among anaerobic physical efforts and, with minor magnitude, by long-duration aerobic exercise, this hypothesis is reinforced by the obtained data, being higher the Mo values among all sportsmen (of all modalities) than among CG.…”
Section: Discussionmentioning
confidence: 67%
“…Bergeret al [ 23 ], found similar results among marathon runners, but, in their case, without the reference of a control group. Augmented Mo concentrations would ease the formation of uric acid as well as decrease the damage caused by superoxide anions generated by xanthine oxidase in the ischemia-reperfusion processes, situation induced by high intensity muscular activities [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Marocolo et al (32) shows the majority of studies demonstrating beneficial effects of IPC did not include a sham condition. Although true blinding in IPC studies is difficult because the pressures typically used for IPC and sham feel very different (12,27), the perception of whether the discomfort that may accompany IPC is detrimental or beneficial is unknown (21). Nonetheless, it is important that the subjects are unaffected by the researchers potential bias, which can be done by blinding the researchers (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the current investigation, all athletes reported having integrated intense priming exercises to their warm-up routine ( Table 1 ). Therefore, since physical activity may elicit a similar preconditioning response to RIPC/IPC ( Lalonde et al, 2015 ; Salvador et al, 2015 ), it is plausible that the effect of RIPC on performance and local metabolism are limited in field studies that investigate elite athletes who typically perform complete warm-up routines ( McGowan et al, 2015 ; Richard and Billaut, 2018 ).…”
Section: Discussionmentioning
confidence: 99%